The translation of Islamic cultural references from Arabic into Spanish: A Descriptive Case Study of Munif' Sirat Madina - Al Duweiri, Hussein (Dirasat: Human and Social Sciences, 2021)
This paper is a descriptive study that is based on the analysis of the translation of the cultural references of Islamic religious character in the translation of Abderrahman Munif novel Sirat Madina into Spanish "Memoria de una ciudad". This paper aims at exploring how this type of cultural references is dealt with in the translation of literary texts from Arabic into Spanish. In order to get an overview of the prevailing strategies in literary translations: domesticating or foreignizing, the present research investigates the translation techniques (functional, literal, paraphrastic, loan, etc.) used by professional translators when handling Islamic terms and expressions. The present paper reveals the clear tendency towards the use of domesticating strategy in the translation of Munif's novel.